(untitled) (American Journal of Pedagogical and Educational Research, 2024)
Innovative approaches to enhancing the speech skills of military students are crucial for their effective communication in various operational contexts. Given the diverse nature of military operations and the need for clear and concise communication, exploring innovative methods to improve speech skills can greatly benefit military personnel. These approaches might encompass a range of techniques, including technology-based solutions, experiential learning, tailored training programs, and interdisciplinary collaborations. By employing innovative strategies, military educators can better equip students with the communication abilities necessary for success in their roles.